2013
DOI: 10.1002/adfm.201201353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exchange Interactions on the Coercivity of SmCo5 Nanoparticles Made by Cluster Beam Deposition

Abstract: Single crystal SmCo5 nanoparticles with an average size of 3.5 nm are produced by cluster-beam deposition. When deposited without matrix, the nanoparticles showed a super-paramagnetic behavior with a blocking temperature of 145 K. Dispersion of the SmCo5 nanoparticles in a carbon matrix results in an increase in both the coercivity and the blocking temperature. Room temperature coercivities as high as 12 kOe are obtained for the first time in mono-layers of SmCo5 nanoparticles dispersed in C matrix. δM plots s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…1e. Moreover, in comparison with the SMP magnet, the switching field distribution (SFD)283334 for the MMP sample is much narrowed, suggesting a more uniform magnetization reversal behavior. Consequently, single peak in μ 0 χ irr , concentrated SFD, complemented with high squareness of demagnetization curves, unveil that magnetostatic interaction plays a dominant role on the “uniform” magnetization reversal of the MMP magnets.…”
Section: Resultsmentioning
confidence: 96%
“…1e. Moreover, in comparison with the SMP magnet, the switching field distribution (SFD)283334 for the MMP sample is much narrowed, suggesting a more uniform magnetization reversal behavior. Consequently, single peak in μ 0 χ irr , concentrated SFD, complemented with high squareness of demagnetization curves, unveil that magnetostatic interaction plays a dominant role on the “uniform” magnetization reversal of the MMP magnets.…”
Section: Resultsmentioning
confidence: 96%
“…O. Akdogan et al 15 reported the effect of exchange interaction on the coercivity of SmCo 5 NPs. Carbon layers were used to increase the distance of the SmCo 5 NPs in order to reduce the interactions among NPs.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is significant not only to our understanding of nature, but also to our current technology as efforts continue to create smaller and smaller devices. Previous studies revealed novel behavior in the optical and magnetic properties as the size of the system is decreased (Andres et al 1989;Schneider et al 1990;Gavrin et al 1990; Akdogan et al 2012Akdogan et al , 2013. Of fundamental importance is the behavior of the Curie temperature in ferromagnetic systems.…”
Section: Introductionmentioning
confidence: 99%